Carbon-13 and proton magnetic resonance of mouse muscle. - Fung, B M (1977)
It is shown that roughly 4 mmol carbon atoms/g mouse muscle can give rise to a "high resolution" 13C NMR spectrum. From the 13C spectrum, it is estimated that the protons from mobile organic molecules or molecular segments amount to 6-8%of total nonrigid protons (organic plus water) in muscle. Their spin-spin relaxation times (T2) are of the order of 0.4-2 ms. At 37 degrees C, the proton spin-echo decay of mouse muscle changes rapidly with time after death, while that of mouse brain does not.